Memory Strategies Used by Mathematics Students at Dayanu Ikhsanuddin University - Esa Penilta Amiruddin (International Journal of Integrative Sciences, 2023)
Mathematics students used memory strategies. The objective of the research was to find out the use of memory strategies by mathematics students. This research used descriptive qualitative method. The sample of this research was 10 mathematics students in the academic year 2022-2023. The findings showed the learners had different approaches to applying associating and elaborating strategy. It depended on their learning goals and preferred learning styles. Learning from social media and movies was used to increase vocabularies, and learning from music was used to pronounce English correctly. The learners used a mental picture by remembering the situation on social media such as Facebook, Instagram, movies, songs, or situations when playing a game